Pandemic Love and Loss in Armitage's “Lockdown” - Gartaula, Sudeep (KMC Research Journal, 2024)
Simon Armitage's poem “Lockdown” reveals human need and loneliness while examining themes of love and loss during the COVID-19 pandemic. This paper draws parallels between these themes and the separation of Emmott Syddall and Rowland Torre during the Eyam plague. It also compares the poem with Kalidasa's Meghaduta, in which an exiled yaksha sends a cloud to express his love to his estranged wife. Both works reflect the common feelings of longing and separation. By linking Eastern and Western literary traditions, the article emphasizes the universal human experience of longing and the enduring power of love in the face of hardship. It also explores Nietzsche's Apollonian and Dionysian duality in the poem, contrasting chaos and order in the times of crisis.